Factors Affecting Students’ Speaking Skills in Aviation English: Grammar, Vocabulary and Pronunciation Mastery - Fitri Masito; Zusnita Hermala; Vidya Selasdini (Dinasti International Journal of Education Management And Social Science, 2024)
Previous research or pertinent studies are essential for a scientific article or research paper. This article reviews the factors influencing students' ability to speak English in the aviation field, focusing on the mastery of speech, vocabulary, and pronunciation. This study is a comprehensive literature review in the domain of English language learning. The objective of this article is to construct a hypothesis regarding the inter-variable influence for conducting further research. The findings of this literature review indicate that: 1) Students' speaking abilities in Aviation English are significantly influenced by their linguistic mastery, which encompasses grammar, syntax, and overall language structure; 2) Their proficiency in Aviation English is also heavily dependent on their vocabulary, specifically the technical and industry-specific terms used in aviation; and 3) Their pronunciation in Aviation English plays a crucial role in their overall speaking abilities, impacting their clarity, intelligibility, and effective communication in professional aviation settings. This review aims to provide a foundation for future studies to explore these interrelated factors in greater depth.